The Development of a Local Wisdom–Based Dance Learning Module to Improve Elementary School Students’ Learning Outcomes: Pengembangan Modul Pembelajaran Seni Tari Berbasis Kearifan Lokal untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Maisarah, Maisarah; Ilyas, Ilyas; Ilham, Ilham; Idhar, idhar; Damayanti, Putri Surya (Jurnal Evaluasi dan Kajian Strategis Pendidikan Dasar, 2026)
This study addresses the limited availability of learning materials that connect elementary dance instruction to students’ own local culture. The research developed a local-wisdom-based dance learning module (Dompu; Bongi Monca) and examined its validity, practicality, and effectiveness within the Merdeka Curriculum. The study used research and development with the ADDIE model (Analyze–Design–Develop–Implement–Evaluate). A limited try-out involved 19 fifth-grade students of SD Negeri 27 Woja in the 2022/2023 academic year. Data were collected using expert validation sheets (content and instructional design), student practicality questionnaires, learning outcome assessments, observations, interviews, and documentation. Descriptive analysis used percentage scores and mean achievement scores (0–100). The module was very valid (average validity score = 93%) and practical (student practicality score = 77%). Effectiveness was reflected in students’ mean achievement scores: 71 (cognitive), 81 (affective), and 79 (psychomotor), categorized as effective. Overall, the module supports contextual dance learning and strengthens students’ appreciation of local culture.